Calon-Welten: Eine Ethnografie über das Leben, Sterben und Weiterleben bei Ciganos in Brasilien - Vilar, Márcio (transcript, 2020)
How do Ciganos in Brazil act in the context of mourning? This ethnography deals with the creation of "Cigano life" in the midst of others' worlds.